Tratamiento contable de los costos de producción en las microempresas manufactureras - Gorotiza López, Lady Marisol (2021)
The present research work has been directed to the microenterprises of the manufacturing sector, given the need that these types of companies have to recognize and properly assign the costs incurred in the different production lines. Since, it was taken as a reference to a microenterprise dedicated to the manufacture of clothing, the same one that had shortcomings when determining the real costs incurred in the manufacturing process, being empirically managed for this reason its real situation in the financial field. Consequently, the research is supported under a mixed approach, using the non-experimental field design, so since it is a business-type research, primary data were obtained, considering the interview and observation as the most efficient techniques. For the gathering of information….....